1986
DOI: 10.1104/pp.82.1.226
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Second Role for Calmodulin in Biological Clock-Controlled Processes of Euglena

Abstract: ABSTRACIThe response of the Euglena gradiis (Klebs strain Z) photosynthesis circadian rhythm to three calmodulin antagonists was examined. In the presence of an antagonist, the photosynthetic reactions were uncoupled from the biological clock. Instead of the highly predictable rhythmic pattern characteristic of a biological clock-controlled circadian rhythm, the photosynthetic rate appears to be influenced by the light/dark cycle. The rate of 02 evolution increases throughout the light portion of the cycle and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1988
1988
1994
1994

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…At present no factor has been isolated which is evidentially involved in the regulation of oscillating patterns. A possible role in controlling the process of the "biological clock" in Euglena was proposed for calmodulin [10]. Further experiments and detailed analyses may bring some more insight into the molecular mechanisms of the "biological clock" in plants.…”
Section: Plastid and Nuclear Encoded Photosynthesisspecific Genesmentioning
confidence: 99%
“…At present no factor has been isolated which is evidentially involved in the regulation of oscillating patterns. A possible role in controlling the process of the "biological clock" in Euglena was proposed for calmodulin [10]. Further experiments and detailed analyses may bring some more insight into the molecular mechanisms of the "biological clock" in plants.…”
Section: Plastid and Nuclear Encoded Photosynthesisspecific Genesmentioning
confidence: 99%
“…These results were interpreted to mean that in this population of cells, the biological clock no longer regulated the rate of oxygen evolution in the second half of the light cycle. The uncoupling of the oxygen evolution rhythm from the clock was mimicked in control cells by exposure to calmodulin antagonists (12). This observation suggested that calmodulin participated in the steps connecting the photosynthetic reactions to the biological clock and promoted a further examination of the role of calcium in the transducing steps.…”
Section: Introductionmentioning
confidence: 87%
“…a continuous increase in the rate of 02 evolution throughout the light portion of the light/dark cycle (12). When cells were followed for four consecutive days, the normal rhythm in 02 evolution was not observed ( 12), which argues against a phase delay or a transient inhibition in the expression ofthe rhythm. In addition, a naturally occurring population of Euglena gracilis was isolated in which the photosynthetic reactions were not controlled by or coupled to the biological clock but were, instead, influenced only by environmental parameters ( 13).…”
Section: Involvement Of the Dag Signaling Systemmentioning
confidence: 95%
See 2 more Smart Citations